2022
DOI: 10.1002/anie.202211578
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Homologation of Carbonyl Compounds for Iterative Syntheses

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…25 Scheme 1 Development of diazo cycloadditions from tosylhydrazone as a safe precursor and their application in metal free cyclopropanation reactions. 19,24,26 Faculty of Chemistry and Pharmacy, University of Regensburg, Universita ¨tsstraße 31, Regensburg 93040, Germany. E-mail: burkhard.koenig@chemie.uniregensburg.de † Electronic supplementary information (ESI) available.…”
mentioning
confidence: 99%
“…25 Scheme 1 Development of diazo cycloadditions from tosylhydrazone as a safe precursor and their application in metal free cyclopropanation reactions. 19,24,26 Faculty of Chemistry and Pharmacy, University of Regensburg, Universita ¨tsstraße 31, Regensburg 93040, Germany. E-mail: burkhard.koenig@chemie.uniregensburg.de † Electronic supplementary information (ESI) available.…”
mentioning
confidence: 99%
“…Then, treatment with Cs 2 CO 3 under photochemical irradiation (low-energy UV light, 385 nm, 0.5 W) in the presence of an aldehyde 107 leads in MeCN to the corresponding extended branched carbonyl compound 108 starting from ketones; or leads to ketone 109 in the presence of BnEt 3 NCl as a phase transfer catalyst (PTC, it is believed to improve the solubility of the deprotonated hydrazone salt 109 ) in DMSO starting from aldehydes (Scheme 21a). 97 Mechanistically, the reaction is proposed to involve the UV-mediated excitation of the hydrazone salt 110 , which evolves to the corresponding diazo compound 111 , followed by reaction with the aldehyde 107 , thus forming intermediate 112 . This species presumably undergoes a thermally promoted 1,2-H shift leading to the final carbonyl compound 108 or 109 (Scheme 21b).…”
Section: Donor–donor Diazo Compoundsmentioning
confidence: 99%
“…An additional particularly interesting example involving donordonor diazo compounds has been more recently described by Ko ¨nig and co-authors, who have shown an ''assembly line'' strategy to synthesize more complex aldehydes and ketones via a photochemical variant of the Bu ¨chner-Curtius-Schlotterbeck reaction. 97 The authors started by converting aldehydes or ketones 105 to the corresponding tosyl hydrazones 106. Then, treatment with Cs 2 CO 3 under photochemical irradiation (lowenergy UV light, 385 nm, 0.5 W) in the presence of an aldehyde 107 leads in MeCN to the corresponding extended branched carbonyl compound 108 starting from ketones; or leads to ketone 109 in the presence of BnEt 3 NCl as a phase transfer catalyst (PTC, it is believed to improve the solubility of the deprotonated hydrazone salt 109) in DMSO starting from aldehydes (Scheme 21a).…”
Section: Alkyl-alkyl Diazo Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of these methods are, however, restricted on the reactivity of metal-bound or free-singlet carbene intermediates, which are commonly accessed from aryl diazoacetates, diazoacetates, and aryl aryl diazoalkanes (Scheme a). Applications of dialkyl diazoalkanes in carbene transfer reactions remain scarce, and existing approaches employ, for example, the UV light photolysis of oxadiazolines under continuous-flow conditions, yet with limitations in general applicability because of the nature of the strong light source. , In this context, the Gryko group recently disclosed a study on the photocatalytic reaction of spirocyclic oxadiazolines thatupon triplet sensitizationgives a cyclic triplet carbene that reacts in cyclopropanation reactions with electron-deficient olefins under visible light conditions . In a related context, the Zhang and Bruin groups have reported a series of studies on cobalt-catalyzed carbene transfer reactions of diazoacetates where a metalloradical species is involved to achieve cyclopropanation reactions without participation of a conventional singlet carbene intermediate (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%